Analisis Perencanaan Tebal Lapis Perkerasan Kaku (Rigid Pavement) (Studi Kasus: Jalan Tanjakan Dramaga, Kabupaten Bogor) - Darmayuda, Trisna; Rulhendri, Rulhendri; Alimuddin, Alimuddin; Lutfi, Muhamad; Sudrajat, Endang (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2024)
Tanjakan Dramaga road section is a means of land transportation that is devoted to access Pesantren, Tamansari, and Gunung Salak Tourism, which is currently experiencing damage at several points including damage to potholes due to overflow of water from drainage channels that are not functioning properly, asphalt that is damaged and peeling, and the loads of passing vehicles. To Improving the effectiveness and it is necessary to have an appropriate treatment that can overcome the damage to the road segment and so that the road can last a long time, this study Analyze of road stiffness using the standard AASHTO (American Association of State Highway and Transportation Officials) method, and geometric calculations of road conditions using the AASHTO (American Association of State Highway and Transportation Officials) standard and 2002 Bina Marga. The results of the analysis obtained thickness according to the conditions of nine tables AASHTO 1993 is 26 cm with longitudinal reinforcement D12-300 mm, transverse reinforcement D31-840 mm, Dowel or Tie bar used with a diameter of 12 mm, a length of 650 mm, and a distance of 300 mm and the geometric results of the road analysis are full circle. Keywords : AASHTO 1993, Rigid Pavement, Geometric Road